Identification and evaluation of bioflocculant from Bacillus salmalaya 139SI for its application in wastewater treatment / Zayed M. M. Abu Tawila - Zayed M. , M. Abu Tawila (2019)
Bioflocculants are flocculating compounds produced by microorganisms during their growth and has recently received extensive consideration from researchers due to their biodegradable, non-toxicity and lack of secondary pollution from degradation intermediates characteristics. The production, optimization, and Characterisation of bioflocculant QZ-7 produced by a novel Bacillus salmalaya strain 139SI which was isolated from a private farm soil in Selangor, Malaysia, were determined. Meanwhile, the optimal culture condition for bioflocculant production was achieved after cultivation at 35.5 °C for 72 h at pH 7, with an inoculum size of 5% (v/v) and sucrose, glucose as carbon source and yeast extract, urea as nitrogen sources. A bioflocculant yield of 2.72 g was recovered from 1 L of broth culture, with maximum flocculating activity that was found to be 92.6%. Chemical analysis revealed that the pure bioflocculant QZ-7 consisted of 79.08% carbohydrates and 15.68% proteins. Infrared spectrometry analysis showed the presence of carboxyl (COO-), hydroxyl (-OH), and amino (-NH3) groups, which are typically from polysaccharides and proteins. The NMR spectroscopy analysis confirmed the result of FTIR, through the presence of functional groups of the QZ-7. Scanning electron microscopy (SEM) analysis showed that QZ-7 exhibited a clear crystalline brick-shaped structure. The average molecular weight of the bioflocculant QZ-7 was calculated to be 5.13×105Da. LC-MS analysis confirmed that QZ-7 was a glycoprotein compound detected at 741m/z–745m/z. Moreover, the presence of glucose at 182.96 m/z, rhamnose at 354.3m/z, and glucuronic acid at 212.8 m/z. SEM- EDX analysis indicated the existence of C, O, N, P and S in this macromolecule as 55.74%, 42.74%, 0.54%, 0.93% iv and 0.06%, respectively. Thermogravimetric analysis (TGA) of the bioflocculant QZ-7 contained thermos-stable and thermo-labile molecules. Bioflocculant QZ-7 exhibited wide pH stability that ranged from 4 to 7, with a flocculation activity of more than 70%. In addition, QZ-7 was thermally stable and retained more than 80% of its flocculating efficiency after being heated at 60 °C for 30 min. The highest bioflocculating activity of 93.6% was obtained for Ca+2 at 2 mg/L of QZ-7 concentration at pH 7. The treatment of river water by purified bioflocculant QZ-7 showed high performance in the removal of turbidity, total suspended solids and COD. After treating the wastewater, the bioflocculant QZ-7 showed significant flocculating performance with a COD removal efficiency of 93%, whereas a BOD removal efficiency of 92.4% was observed in the B. salmalaya strain 139SI. In addition, results for the removal of heavy metals from industrial wastewater revealed that the bioflocculant QZ-7 was capable of removing the heavy metals. For example, the maximum adsorption of As (89.8 %), and Zn+2 (77.4 %), and Cu+2 (58.4%). Moreover, the bioflocculant QZ-7 had significant removal efficiency of different pharmaceutical compounds, such as Simvastatin (92.45%), Salbutamol (88.69%), Acetaminophen (69%), and Caffeine (66.52%). Furthermore, B. salmalaya 139SI strain and pure bioflocculant QZ-7 could synthesise AgNPs. Also, an antibacterial activity of the AgNPs was detected against test bacterial strains, such as Escherichia coli ATCC35401, Salmonella enteritidis ATCCBAA-711, Staphylococcus aureus ATCC2592 and Pseudomonas aeruginosa, as application of AgNPs.